Harnessing the potential of multimodal radiotherapy in prostate cancer - Philippou, Y; Sjoberg, H; Lamb, AD; Camilleri, P; Bryant, RJ (Springer Nature, 2020)
Radiotherapy in combination with androgen deprivation therapy (ADT) is a standard treatment option for men with localized and locally advanced prostate cancer. However, emerging clinical evidence suggests that radiotherapy can be incorporated into multimodality therapy regimens beyond ADT, in combinations that include chemotherapy, radiosensitizing agents, immunotherapy and surgery for the treatment of men with localized and locally advanced prostate cancer, and those with oligometastatic disease, in whom the low metastatic burden in particular might be treatable with these combinations. This multimodal approach is increasingly recognized as offering considerable clinical benefit, such as increased antitumour effects and improved survival. Thus, radiotherapy is becoming a key component of multimodal therapy for many stages of prostate cancer, particularly oligometastatic disease.